Caring for Weary Souls: A Critical Examination of Church Involvement in Congregation Mental Health Issues - Hia, Budieli; Gultom, Rogate Artaida T; Damanik, Dapot (Tinta Emas Institute, 2025)
This study discusses the role of the church in addressing mental health issues among congregants. It begins by highlighting the growing awareness of mental health struggles within the Christian community and the broader society. Despite this growing concern, many churches remain unprepared to provide adequate pastoral care for individuals experiencing psychological distress. The paper examines theological perspectives and pastoral practices that influence the church’s response to mental health challenges. Using literature review and contextual reflection, the author explores the tension between spiritual assumptions and psychological realities. The study emphasizes the need for the church to cultivate a more empathetic and holistic approach to care. Rather than pathologizing mental illness or relegating it solely to spiritual causes, churches are encouraged to create safe, supportive spaces for healing and restoration. This paper offers a foundational framework for developing a contextual theology of mental health that is both practical and compassionate.